Gastric emptying rate in subjects with malocclusion examined by [13C] breath test. (15th May 2013) - Koike, S.; Sujino, T.; Ohmori, H.; Shimazaki, K.; Fukuyama, E.; Kanai, T.; Hibi, T.; Ono, T.
Summary Masticatory function is significantly lower in individuals with malocclusion than in those with normal occlusion. Although several studies suggest that masticatory function influences gastrointestinal digestive function, the relationship between malocclusion and gastrointestinal symptoms has not been studied extensively. We hypothesised that insufficient masticatory function would increase the functional burden of the stomach and have some influence on the gastrointestinal system. The purpose of this study was to investigate masticatory function and gastric emptying rate in subjects with malocclusion. Eleven healthy dentate female volunteers and eleven female patients with maloc‐clusion underwent a 13C‐acetate breath test with a liquid meal. Maximum 13CO2 exhalation time (Tmax) was compared statistically between both groups. Masticatory function was assessed by colour‐changeable chewing gum. In addition, the frequency scale for the symptoms of gastroeso‐phageal reflux disease (FSSG) and questionnaires on food intake were given to both groups. The mean Tmax of the malocclusion group was significantly longer than that of the normal occlusion group (P = 0·007). Masticatory performance, measured by colour‐changeable gum and questionnaires, was significantly lower in the malocclusion group than in the normal occlusion group (P = 0·023, P = 0·003). There was no significant difference in the FSSG results between the two groups (P = 0·262). This study suggested that there was a correlation between malocclusion and gastric emptying function in women.